ANALISA PERUBAHAN SOSIAL DALAM MODERNISASI BUDIDAYA TANAMAN PADI (Oryza sativa) DI KECAMATAN SECANGGANG KABUPATEN LANGKAT PROVINSI SUMATERA UTARA - Dwi Febrimeli; Ameilia Zuliyanti; M. Bhakti Triyoga (Hasanuddin University, 2020)
This study aims to determine the level of social change and the factors that influence the modernization of lowland rice cultivation in Secanggang District, Langkat Regency. The data collection method used is the method of observation, interviews, documentation and questionnaires that have been tested for validity and reliability. Furthermore, 69 samples were tested using a Likert scale with multiple linear regression methods using SPSS version 20.00. The results showed that the level of social change was 89.69% with a very high category. There is a significant influence between cultural values, community behavior patterns, community institutions, and socio-economic relations in Telaga Jerni Village, Secanggang Village and Tanjung Ibus Village (F> 0.05 = 10,759).